LANDSCAPES AND ENVIRONMENTS OF THE MIDDLE AGES - Bintley, Michael D. J., author. (London)
1 online resource
Keywords: This book is a comprehensive introduction to the landscapes of the Middle Ages within and beyond Europe, paying close attention to the relationship between real' and imagined landscapes and the ways that medieval people made and inhabited their world. Rather than studying 'nature' in the Middle Ages, the book instead examines the spaces that people constructed through soil, stone, and song; water and wasteland; plants and animals; and timber, textiles, and texts, which in turn made up the medieval world. Likewise, the text emphasises a definition of environment that focuses on living with', inviting readers to think about the more-than-human worlds that medieval people depended on, cared for, constructed, and damaged. Bringing together a wide range of primary source material, including evidence from texts, material culture, and visual arts, the book reflects the diversity of landscapes and human responses to them throughout the course of this period and considers the role that these medieval worlds have played in shaping the modern, both physically and culturally. Landscapes and Environments of the Middle Ages is an excellent resource for both undergraduate and postgraduate students in medieval studies and history, offering interdisciplinary, transhistorical, and transnational insights into this period of immense change and innovation.